Cancer with unknown primary: finding a needle in a hay stack - Giesel, F.L.; Mehndiratta, A.; Mafomane, M.P.; Zechmann, C.M.; Bergmann, F.; Schemmer, P.; Haberkorn, U.; Kratochwil, C. (Experimental Oncology, 2012)
Detection and resection of small neuroendocrine tumours (NET) is like finding a needle in a hay stack. Use of specific tracers such as 68Ga-DOTATOC in a PET/CT study has been proven to have a high sensitivity and specificity to cells expressing somatostatin-SSR receptors. The use of 99mTc-Octreotide to detect neuroendocrine tumours during surgery is an effective adjunct for therapy. We here present a clinical case of patient with NET where these modalities help in both diagnostic and therapeutic surgery.